Direct and Indirect Effects of Resource P-Limitation Differentially Impact Population Growth, Life History and Body Elemental Composition of a Zooplankton Consumer - Zhou, Libin; Lemmen, Kimberley D.; Zhang, Wei; Declerck, Steven A. J. (Frontiers in Microbiology, 2018)
One of the central tenets of ecological stoichiometry is that consumer growth rate is strongly determined by food phosphorus (P) content. In planktonic organisms population growth rates of zooplankton have repeatedly been shown to be reduced when fed with P-limited algal food sources. However, P-limitation may also affect other quality-related aspects of algae, such as biochemical composition or palatability. We studied the population growth, detailed life history and body elemental composition of the herbivorous rotifer, Brachionus calyciflorus, in response to three different food quality treatments: algae cultured in high phosphorus conditions (average algal molar C:P ≈112,‘HP’), algae cultured in low P conditions (molar C:P ≈ 631, ‘LP’) and low-P cultured algae spiked with P just before feeding (molar C:P ≈113, ‘LP+P’). LP+P algae thus combined high P content with a history of growth under P-limited conditions. Total P content and the C:P ratio of rotifers in the LP+P treatment equaled those of rotifers in the HP treatment. Rotifer population growth rates were higher in HP than in LP and intermediate in the LP+P treatment. Similarly, many life history traits observed for animals in the LP+P treatment, such as somatic growth rate, age at maturity, and egg production rate were also intermediate to those observed in the LP and HP treatments. However, there were important deviations from this pattern: size at first reproduction and egg mortality in the LP+P treatment equaled the HP treatment, whereas size and development time of the first eggs equaled those of the LP treatment. Our results indicate that elemental limitation cannot fully explain reduced performance of consumers fed with P-limited algae and strongly suggest that indirect, non-stoichiometric effects of P-limitation, e.g. via changes in biochemical composition or morphology of the algae also play a major role. Furthermore, our study highlights that such indirect effects have a differential impact on major fitness components and may as such also determine the population dynamics and demographic structure of consumer populations.